A STUDY ON THE ABILITY OF THE FOURTH SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM OF FKIP-UR IN WRITING AN EXPOSITORY ESSAY - Muhaimin, Rosyidah; Elirwati, Elirwati; Masyhur, Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: As a productive skill, writing is considered a difficult subject for the students. It needs practicing to improve the ability. It is important for English learners of education faculty to acquire writing as a basic skill to face the global needs of communication in future life. Since expository is the common type of writing used in university, the students are expected to be able to write a good expository writing. This descriptive quantitative research is aimed at finding out the ability of the fourth semester students of English Study Program, FKIP-Universitas Riau in writing an expository essay. The samples of the research are 34 fourth semester students in academic year of 2017/2018 who are chosen by using cluster random sampling technique. The data are obtained from students’ performance in expository writing. There are 5 topics provided with several types of essay development; descriptive, chronological order, cause & effect, comparison & contrast and persuasion in which the students have to choose one to hand in. The time allocation is 120 minutes for the entire test. The data are graded by four raters by using analytical scoring system that assesses some aspects of writing; grammar, vocabulary, mechanics, fluency and organization. The finding shows that the students have good ability level in writing an expository essay with the mean score of 67,90. Besides, it is found out that the students’ ability in terms of organization is the highest among other aspects with the mean score of 72,50. The lowest score is in terms of mechanics with the mean score of 65,44. This study suggests that the students need to do more practice and be concerned more toward every aspect of writing, particularly in terms of mechanics and grammar.Keywords: Study, Writing Ability, Expository Essay